Kelayakan Usahatani Padi Varietas Unggul Baru Melalui PTT di Kabupaten Halmahera Tengah - Hidayat, Yayat; Saleh, Yopi; Waraiya, Musa (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Increasing rice production in isolated areas of the Central Halmahera District, North Maluku Province, is expected to strengthen food security as well as increasing farmers’ income. The objective of the study was to identify technology for increasing rice productivity in the lowland rice farming. An experiment was conducted at Sumbersari Village, Central Halmahera District, North Maluku Province, from July to October 2010. Four treatments consisted of four high yielding rice varieties (Inpari2, Inpari3, Inpari7, and Silugonggo) were cultivated applying the integrated crop management (ICM) and one variety (Cigeulis) was grown applying the local farmer’s practice as control. The experiment was arranged in a randomized complete block design with three replications. Results showed that yield of cultivar Inpari 2 (7.15 t harvest dry grains (HDG)/ha), Inpari 3 (6.29 t HDG/ha), Inpari 7 (6.35 t HDG/ha), and Silugonggo (5.23 ton HDG/ha) were higher than that of Cigeulis variety (4.69 t HDG/ha). The R/C ratios of the ICM was higher than that of the conventional crop management, namely for Inpari 2 1.95, Inpari 3 1.72, Inpari 7 1.75, and Silugonggo 1.43, whereas the non-ICM (Cigeulis) was 1.49. The seed advantage value for the respective varieties was 2.14, 1.62, 1.65, and 1.02, respectively, each was higher than 1. This study indicated that introduction of new varieties into the ICM system increased rice productivity by 0.54-2.46 t/ha and increased farmers’ incomes by Rp 1 to 3 million/ha. This meant that the adoption of new rice variety applying the ICM system in Central Halmahera, North Maluku, could be recommended for increasing rice production and farmers’ income.